Britain's retreat from empire in East Asia, 1905-80 - Best, Antony (Routledge studies in the modern history of Asia, 2017)
The decline of British power in Asia, from a high point in 1905, when Britain's ally Japan had vanquished the Russian Empire, apparently reducing the perceived threat that Russia posed to British interests in India and China, to the end of the twentieth century, when British power had dwindled to virtually nothing, is one of the most important themes in understanding the modern history of East and Southeast Asia. This book considers a range of issues that illustrate the significance and influence of the British Empire in Asia and the nature of Britain's imperial decline.